Nanotechnology-Based Histone Deacetylase Inhibitors for Cancer Therapy - Tu, Bin; Zhang, Meng; Liu, Tuanbing; Huang, Yongzhuo (Frontiers in Cell and Developmental Biology, 2020)
Histone deacetylase inhibitors (HDACi) have been approved and achieved success in hematologic malignancies. But its application in solid tumors still confronts big challenges and is hampered by low treatment efficacy. Nanotechnology has been widely applied in cancer therapy, and nanomedicine could improve drug stability, prolong the circulation half-life, and increase intratumoral drug accumulation. Therefore, nanomedicine is a promising strategy to enhance HDACi therapy efficacy. The review provides a summary of the advances of HDACi nanomedicines with a focus on the design principles of the targeting delivery systems for HDACi.